Determinacion del azucar preferencial en la dieta de Lutzomyia evansi (Nuñeztovar) (Diptera: Psychodidae) - Bastidas P, G.=700 1 Oviedo, M.; Vivenes J, A.; Gonzalez, A.
(Es, En)
Ilus., 22 ref.
Keywords: LUTZOMYIA; DIETA; AZUCARES REDUCTORES; LEISHMANIA; COLOMBIA; LEISHMANIOSIS